Framing Educational Policies: The media as political actors in education - Cabalin, Cristian (Estudios sobre el Mensaje Periodístico, 2013)
This article describes the relationship between journalistic and educational fields via a case study of the 2011 Chilean student movement. Considering the above, this study analyzes the editorials of two of the most influential newspapers in Chile in order to describe their roles as political actors in the educational debate during the student movement. Through the implementation of mixed methods (content analysis and discourse analysis), it was found that the editorials focused on the political repercussions of the conflict, emphasizing the actions that the political system should take. The discourse of the editorials defended the privatization initiative in education by placing the blame on public education for its current state and it also framed the educational problem as a temporary situation, ignoring its systemic nature.
Keywords: Framing; discourse; politics; education; editorials.